Factors affecting inflation in Malaysia / Nabila Hanis Abdul Rahman - Abdul Rahman, Nabila Hanis (Faculty of Business and Management, 2018)
Inflation became a one of the serious matters over a period of time. It can be said that, throughout the past few years, Malaysia’s inflation is caused by many factors. This paper investigates the relationship between inflation and the other factors such as Money Supply (MS), Exchange Rate (ER), Interest Rate (IR) and Gross Domestic Product (GDP) in Malaysia over the period from 1986 to 2016. Autoregressive Distributed Lag (ARDL) model has been employed to find cointegration among variables of the models. Trade off exists between all the independence variables over short run and long run with inflation rate. The results reveal that inflation rate in Malaysia will react positively towards the change in money supply, exchange rate, interest rate, and gross domestic product. Gross Domestic Product is revealed as major cause of inflation while interest rate is found to be a minor cause of inflation.